Congress, the Supreme Court, and Religious Liberty: The Case of City of Boerne v. Flores - Waltman, Jerold L. (Palgrave Macmillan, 2013)
In the case City of Boerne v. Flores, the Supreme Court struck down the Religious Freedom Restoration Act of 1993. Waltman offers the first book-length analysis of the act to show how this case contributes to an intense legal debate still ongoing today: Can and should the Supreme Court be the exclusive interpreter of the Constitution?